ЗАХИСТ ВІД НАДНАПРУГ РОЗІМКНЕНОГО ВТОРИННОГО КОЛА ТРАНСФОРМАТОРА СТРУМУ - Журахівський, А. В. (Вісник Вінницького політехнічного інституту, 2017)
The article describes the results of research of operating modes of the protection system of the open secondary circuit of the current transformer against overvoltages. The research was carried out by using the laboratory experiment and computer simulation. A comparative analysis of the obtained results by using the laboratory experiment and computer simulation in order to assess the efficiency of the operation of the proposed protection system with, as an example, the current transformer type TLM-10 was carried out.